Accuracy of Cell-Free DNA (cfDNA) in Colorectal Cancer Diagnosis - Anjab Akmal Sya’roni; Suyata; Imam Supriyanto; Vidi Orba Busro; Ayus Astoni; Mediarty Shahrir; Taufik Indrajaya; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Colorectal cancer is the third most common type of cancer following lung and breast cancer with the second most common cause of cancer-related death globally. Delayed diagnosis due to limited source and modality to perform early diagnosis lead to advanced-stage condition which contributes to higher morbidities and mortalities. Recent diagnosis of colorectal cancer depends on biopsy of suspected tissues, either obtained surgically or per colonoscopy. Colorectal cancer detection through cell-free DNA measurement allowing small-size cancer being detected even in early stage. cfDNA originated from derivates of increased and abnormality apoptosis-necrosis pathway from cancer lesion, therefore can be managed as specific tumor marker. Methods: Diagnostic test was performed at the Gastroentero Hepatology Outpatient Unit and Internal Medicine Inpatient Unit of Dr. Mohammad Hoesin General Hospital Palembang from March to June 2021. Data processing and analysis using SPSS version 26.0 for Windows. Results: Among 50 subjects included, 39 subjects (78%) are diagnosed with colorectal cancer, whereas 11 subjects (22%) as control. The median of cfDNA result is 59,71 ng/mL with 92,3% sensitivity, 90,9% specificity, 95,2% positive predictive value, 82,3% negative predictive value, and 92,4% accuracy rate. Combination the measurement of cfDNA, CEA, and CA19-9 appears to have better AUC instead of single measurement. Conclusion: The study reveals that cell-free DNA (cfDNA) demonstrated a very promising accuracy rate in diagnosing colorectal cancer.